Astaxanthin-loaded polylactic acid-glycolic acid nanoparticles ameliorate ulcerative colitis through antioxidant effects - Li, Chunmei; Zhou, Yu; Yuan, Meng; Yang, Yawen; Song, Ruilong; Xu, Gang; Chen, Gang (Frontiers in Nutrition, 2023)
Introduction Astaxanthin (AST) is a type of carotenoid with strong antioxidant effects. However, the development and use of AST are limited by its water insolubility and low bioavailability. This study aims to investigate whether AST@PLGA can inhibit UC and reveal its possible mechanism. Methods We tested the particle size, polydispersity index, and zeta potential of AST@PLGA. Then, the in vitro release and antioxidant capacity of AST@PLGA were tested. Finally, the mouse model of colitis was established and SOD, MDA, TNF-α, IL-1β, IL-6 and P38 as well as ERK were detected from mice. Results Particle size, polydispersity index and zeta potential of AST @PLGA were 66.78 ± 0.64 nm, 0.247 and -9.8 ± 0.53 mV, respectively, and were stable within 14 days. Then, it was observed that the AST@PLGA nanoparticles not only maintained the effect of AST but also had a sustained release effect. Experiments in mice showed that AST@PLGA effectively reduced MDA, TNF-α, IL-1β and IL-6 levels and increased SOD levels. AST@PLGA also downregulated the protein expression of P38 and ERK. The results showed the positive protective effect of AST@PLGA in inhibiting acute colitis. Discussion AST@PLGA nanoparticles have good stability and alleviating effect in colitis, which could be functional foods in the future.